Measuring Quality of Life: A Case Study of Jabalpur City - Tiwari, Rambooshan; Singh, Jagadish (National Geographical Journal of India, 2022)
Ever- increasing populations in urban areas in general and metropolitan cities in particular, especially in developing countries including India has created myriad urban problems. As a result, quality of urban life has deteriorated significantly. In measuring quality of life (the good life) two approaches i. e. objective and subjective/ perceptual approach have been adopted by scholars in various disciplines. However, in the present paper objective approach based on empirical reality has been adopted to measure quality of life (QoL). Here, objective indicators such as type of house, ownership of house, number of rooms per household and availability of basic facilities within premise of house have been used to calculate quality of life index (QoLI). Based on this index, quality of life has been analyzed across a crosssection of space and society in Jabalpur – a million+ city of India. The paper also brings out some useful suggestions towards improvement in quality of life of the citizens of the city.